Efforts to Increase Student Interest in Learning Through the Application of Learning Model Talking Stick - Henra Saputra Tanjung; Siti Aminah Nababan; Nuraini Sri Bina (Seutia Hukamaa Cendekia, 2023)
This research is to describe the application of the learning model talking stick that can increase students' interest in learning and to describe the activities of teachers and students in implementing the learning model talking stick. The approach taken in this research is qualitative, with the type of research being Classroom Action Research (PTK). The subjects in this research were all class V students of SD Negeri 1 Simpang Peut, Kuala District, Nagan Raya Regency, totaling 23 people. This research procedure uses planning, implementation, observation, and reflection. The data collection techniques used are observation and test techniques. The results of the pre-action research were that only 9 students, or 39.1% completed their learning outcomes with an average score of 58.7. The data from the first cycle test results shows that students who obtained grades> 70 is 13 students or 56.5% with an average score of 68.3, while the data from the second cycle test results show that students who get a score> 70 is 20 students or 86.9% with an average score of 79.6. The results of observations of teacher activities in cycle I were 72.5% included in the good category, while in cycle II, it reached 83.75% in the very good category. The results of observations of student activities in cycle I were 70.8% in the good category, while in cycle II, it reached 80.6% in the very good category. Based on this, applying the learning model talking stick can increase the interest in learning of class V students at SD Negeri 1 Simpang Peut, Nagan Raya Regency.